Analisis Gerakan Literasi Sekolah Terhadap Minat Baca Siswa Kelas II di SD Negeri 185 Palembang - Berliana, Debora; Ferdiansyah, M; Syaflin, Sylvia Lara (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Reading is one of the things that is difficult for some people, including children, because reading is a key to success in weaving education. However, according to Wiradnyana (2018: 27) said that Indonesia is one of the countries that are considered to have a low reading culture. Therefore, it is from elementary school as prospective teachers and those who have become teachers must be able to instill a readingculture in students. In the end, since the 2013 Curriculum was implemented in Indonesia, the Government implemented the School Literacy Movement which is a requirement to support the implementation of the 2013 Curriculum by reading non-lesson books for 15 minutes. Based on this, the problem in this research is how is the process of the School Literacy Movement towards reading interest in second grade studentsat 185 Palembang Elementary School. The purpose of this study was to analyze the process of the School Literacy Movement on reading interest in second grade students at the 185 Palembang State Elementary School. The research method used is descriptive qualitative method. The sampling technique used by the researcher is purposive sampling technique. Collecting data in this research through interviews and documentation. The results of this study can be concluded that the School Literacy Movement has been implemented since the 2013 Curriculum took effect. In any school, the Literacy Movement must be implemented. As in the State Elementary School 185 Palembang, it is one of the schools that has implemented the Literacy Movement by having a reading corner in the classroom and making visits to the library according to the specified schedule. Then, the Literacy Movement at 185 Palembang State Elementary School had a good influence on reading interest in second grade students at 185 Palembang State Elementary School. As the results of the study, as long as the Literacy Movement was implemented,it became a solution to foster interest in reading in students because they experienced an increase in reading.